PENERIMAAN OPINI AUDIT DENGAN MODIFIKASI GOING CONCERN DAN FAKTOR-FAKTOR PREDIKTORNYA - Oka Surya Utama, I Gusti Putu; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
Auditor’s responsibility when identifying the ability of company to maintain their business for long term period (going concern) still to be a phenomenon that rarely revealed cause by accounting manipulation involvement. The case of the liquidated companies that on the previous year received unqualified opinion precisely from independent auditor showed the reality happens. This research has a purpose to analyze and verify about the effect of firm growth, firm size, audit quality, audit lag, audit tenure, and opinion shopping factor on the acceptance of audit opinion with going concern modification in manufacturing company which listed in Indonesia Stock Exchange period 2010-2013. The sample determined by utilizing purposive sampling technique, therefore as many as 84 of observation sample was obtained. The data observed by logistic regression analysis method. The results show that firm growth, firm size, audit quality, and audit tenure did not has effect on the acceptance of audit opinion with going concern modification. However audit lag has positive  effect and opinion shopping has negative effect.
Keywords: going concern audit opinion, firm growth, firm size, audit quality, audit lag, audit tenure, opinion shopping